I want to celebrate as hymns acculturation of i will sing of my redeemer (an analysis on a Sangihe Masamper song) - Glenie Latuni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This research aims to analyze the acculturation process through the hymn I will sing of my Redeemer, which became Hymn MasamperI Want To Celebrate. I will use a qualitative approach to explore the perspective of ethnomusicology and hymnology through observation, interviews, and literature review. Observations have been made for a long time because the researcher is also the artist of Masamper Art. But the focus of observation from 2008 until now has been Observations were made on various Masamper performances in the Sangihe community in the Sangihe Islands and the Sangihe diaspora community on the mainland of North Sulawesi in the city of Manado. The results of the analysis found that the existence of the song "I want to be grateful," Masamper's singing in the Sangihe community, is the result of acculturation from the Hymn. songI will sing of my Redeemer works by Philip Paul Bliss. The results of this acculturation found that there was a change in form from a 3 stanza strophic form to a 1 stanza strophic form, but it is done repeatedly. The bars have also changed from 9/8 bars for the original song to bars for mourning (Masamper Sabuah) and 4/4 bars during party performances or competitions (Mebawalase). The tempo changes from fast to slow but uses stress on each word. Meanwhile, the meter still uses the 8.7.8.7 CM (Common Meter) pattern except for the refrain. The syllabic pattern, or singing with one note for one syllable, is still carried out, but new developments have emerged in the Sangihe community, namely the Manahola singing style, or singing before the main song word, the Mamaranca style of singing repeating words in the verse that are currently being sung, and the Yora style of singing while singing. Do word stresses on the refrain or repetition of the song, which is usually done while dancing.